Méliès Boots Footwear and Film Manufacturing in Second Industrial Revolution Paris - Solomon, Matthew (University of Michigan Press, 2022)
Before he became the father of cinematic special effects, George Méliès (1861-1938) was a maker of deluxe French footwear, an illusionist, and a caricaturist. Proceeding from these beginnings, Méliès Boots traces how the full trajectory of Georges Méliès' career during the late-nineteenth and early-twentieth centuries, along with the larger cultural and historical contexts in which Méliès operated, shaped his cinematic oeuvre. Solomon examines Méliès' unpublished drawings and published caricatures, the role of laughter in his magic theater productions, and the constituent elements of what Méliès called "the new profession of the cinéaste." The book also reveals Méliès' connections to the Incohérents, a group of ephemeral artists from the 1880s, demonstrating the group's relevance for Méliès, early cinema, and modernity. By positioning Méliès in relation to the material culture of his time, Solomon demonstrates that Méliès' work was expressive of a distinctly modern, and modernist, sensibility that appeared in France during the 1880s in the wake of the Second Industrial Revolution.